Understanding Mosquito Faunal Diversity: An Approach to Assess the Burden of Vector-Borne Diseases in Three Representative Topographies (Rural, Urban, and Peri-Urban) of Ganjam District in Odisha State, India - Deepika Panda; Rabi Sankar Pandit; Bijayalaxmi Sahu; Raghavendra Kamaraju; Tapan Kumar Barik (Journal of Tropical Medicine)
Mosquitoes are the best-known disease vectors for most vector-borne diseases that significantly impact global health in terms of morbidity and mortality. In a geographical area, mosquito faunal diversity often alters with changing climatic factors and variable breeding habitats that differ across seasons. Using biodiversity indicators as tools, a study was conducted in rural, peri-urban, and urban areas of district Ganjam, Odisha state, to determine mosquito faunal diversity as an approach to forecast the possible risk of disease transmission in the three representative topographies. A two-year study was undertaken to assess the alpha diversity of mosquito species by the numerical strength of the species using various eco-diversity indices. Species richness and abundance of mosquito species are significantly higher in peri-urban areas compared to urban and rural areas. The species dominance of Culex quinquefasciatus was observed in all three topographies, while Aedes aegypti, Aedes albopictus, and Anopheles stephensi were in urban areas. Species richness may dilute the risk of disease in an area, but increased species dominance, mostly vector species, in a new habitat often allows pathogens to infect newer communities at risk, leading to the emergence of new diseases. The current study indicates the possible risk of lymphatic filariasis (LF) infection in all three topographies. On the other hand, the risk of malaria and dengue/chikungunya transmission is higher in urban areas. With routine entomological monitoring, including vector incrimination, the biodiversity indicators will be the best tool to forecast the risk of vector-borne diseases in an area; accordingly, judicious vector control strategies can be adopted.